Enhanced and integrated geothermal systems for sustainable development of Canada's northern communities. (February 2020) - Mahbaz, S.B.; Dehghani-Sanij, A.R.; Dusseault, M.B.; Nathwani, J.S.
Highlights: Evaluation of sustainable development in Canada's northern regions. Introduction of enhanced and integrated geothermal systems. A first-order technical and economic feasibility study of integration various local energy sources with geothermal energy. Provision of a sustainable solution to meet the long-term energy needs of Northern Canada's remote communities. Abstract: This paper provides an evaluation of the needs and requirement for the provision of critical energy services to communities in Canada's northern region. Enhanced geothermal system concepts are introduced as part of a set of integrated solutions that are cost-competitive and sustainable over the long-term. The goal is to establish a low-carbon energy supply system that not only generates sufficient power and heat to satisfy basic needs but can be scaled to meet higher level requirements for economic empowerment. For remote and isolated communities, a reliable and cost-effective supply of energy is a critical factor to develop and sustain a standard of living comparable to southern regions of Canada. The high cost of energy supply, specifically diesel transport over long distances, is a severe impediment to sustainable development in the northern regions of Canada. A first-order technical and economic feasibility study of the integration of different local energy sources (both renewable and non-renewable) with geothermal energy (deep and shallow) is developed to establish a pathway for a more efficient, low-carbon, sustainable energy sources. The results of this analysis provide a strong basis for investment in modular small-scale integrated geothermal systems for seasonal heat storage and electricity services.